Forutsetninger for vellykket sosial innovasjon i sykehjem: ledernes perspektiv – en kvalitativ intervjustudie - Totcheva, Catherina Øverås; Vedeler, Janikke Solstad; Slettebø, Åshild (Nordisk tidsskrift for helseforskning, 2019)
Preconditions for successful social innovation in nursing homes: Managers' perspectives - a qualitative interview studyIn this article, we investigate preconditions for social innovation in institution-based elderly care in Norway and Denmark. The article draws on two semi-structured interviews and one focus-group interview. The interviewees are managers in elderly-care facilities that are known to be proficient with regards to innovation. The analysis point to three principles managers describe as being pertinent to successful social innovation. Firstly, an overall theme across the interviews was that the managers underscored the importance of eagerness and willingness to change as a prerequisite for innovation. Secondly, the managers claimed that another crucial condition to facilitate innovation is to involve the employees in both the negotiation and the implementation of innovation. Thirdly, the managers reported that they strive to create a learning environment, arguing that learning and social innovation are interrelated terms and should be treated as such.